Modelling the Partial Demineralization Process of Cow Milk by Superpro Designer - Csighy Attila; Koris András; Vatai Gyula (Hungarian Journal of Industry and Chemistry, 2017)
Milk and dairy products contain a number of biologically active compounds (proteins, lipids, vitamins and minerals) that are essential for human nutrition. The most common procedures for demineralization are based on ion exchange-, nanofiltration- and electrodialysis-based technologies. In this study, the application of membrane filtration-based partial demineralization of cow milk was investigated and the process modelled. Using design equations, the partial demineralization process was designed and the economy of the process calculated. The modelling and simulation of the partial demineralization process was carried out by the SuperPro Designer programme. As the first step the unit operations of the demineralization technology were defined using the tools of the programme. The SuperPro Designer possesses industrial tools with reactor models, chemical components, a database of mixtures, and price estimations. By analysing the influence of the operation parameters, the feasibility of the proposed process was investigated. From the results of the modelling it can be concluded that the partial demineralization process can be successfully implemented, achieving the expected demineralization rates with a relatively good payback time of two years.